Applied Cyber Security for Applied Software Engineering Undergraduate Program (Journal of The Colloquium for Information Systems Security Education, 2020)
In the current landscape where a constantly growing number of cyber threats is accompanied by the increasing shortage of cyber security professionals, it is essential to provide a well thought-out hands-on cyber security education as a part of all Computer Science and Software Engineering degrees. This paper described the experience of designing and delivering a Cyber Security module to Level 5 students on a three-year BSc Applied Software Engineering program. The key goal of the module is to instil the importance of cyber security in software development, and to teach in practice modern security techniques. While being predominantly focused on web-application security, the module also covers foundational cyber security concepts, cryptography and network security, and discusses non-technical topics including security frameworks and security economics. The paper presents the outline of the module, the configuration of the virtual machine used, the structure and content of sessions.
Keywords: cyber security education; software engineering; web-application security